Violencia en redes sociales: Ciberbullying en adolescentes usando Facebook e Instagram, primer semestre 2020 - Burgos Quiroga, Ginger Yelena (2020)
The information and communication technologies and their constant evolution impact on all the cultural, social and economic processes in which we are immersed, being this perceptible or imperceptible affectation which becomes a new form of coexistence and interaction, being one of these scopes the virtual. A cyberculture is created where lifestyles, ways of thinking, acting, and relating are promoted, even more so if one considers how indispensable it has become for young people to be a participant in this new form of social bonding, in which they give to know their daily life and their forms of entertainment. Cyberbullying conceptualized as harassment between equals using social or telematic networks, including blackmail, humiliation, insults and ridicule. This study revealed that the aggressions that are experienced in social networks are caused by conflicts, the object of this study is to identify the use that adolescents give to the tools provided by social networks and the effect it has on the communicational behavior of the themselves